2011
DOI: 10.1007/s11748-011-0795-z
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump coronary artery bypass grafting with an aortic nonclamping technique may reduce the incidence of cerebral complications

Abstract: The aortic nonclamping technique might reduce the incidence of cerebral complications and produce ideal bypass grafts using arterial grafts and saphenous vein grafts with a proximal anastomosis device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…They concluded that the aortic nonclamping technique might reduce the incidence of stroke. Kobayashi, et al 38) also reported that there was no operative death or stroke by using an aorta no-touch technique with in-situ graft and composite and sequential grafting methods.…”
Section: Diabetes Mellitus (Dm)mentioning
confidence: 99%
“…They concluded that the aortic nonclamping technique might reduce the incidence of stroke. Kobayashi, et al 38) also reported that there was no operative death or stroke by using an aorta no-touch technique with in-situ graft and composite and sequential grafting methods.…”
Section: Diabetes Mellitus (Dm)mentioning
confidence: 99%
“…Cerebral infarction is a common neurological complication after cardiac surgery [ 9 ], The incidence of recessive cerebral infarction detected by diffusion-weighted magnetic resonance imaging is high as 50% [ 10 ]. Microemboli from cardiac surgery can block blood flow and cause ischemia and capillary loss [ 11 ], and hypoxia.…”
Section: Introductionmentioning
confidence: 99%